An experimental analysis of the risk-trust confound - Chetty, Rinelle (School of Economics, 2017)
The notion of trust has great significance to an economy. Trust is known to be associated with efficient judicial systems, improved government functioning with lower corruption, and better financial outcomes (Johnson and Mislin, 2011). However, many researchers have argued that risk attitudes may confound the measurement of trust because trusting decisions involve outcomes that have only some probability of occurring. This study therefore seeks to question whether risk attitudes predict trusting decisions in the Berg, Dickhaut and McCabe (1995) Investment Game amongst students at the University of Cape Town in 2016. The statistical method adopted is maximum likelihood estimation which accounts for subject errors in decision making. This study finds that having additional information on the past behaviour of trustees does not affect the trusting behaviour of trustors. In addition, the presence of a human trustee, versus a computer, is found to significantly influence behaviour and decisions made by trustors in the trust game. It is also found that subjects are, on average, risk averse with 62% of subjects exhibiting high levels of risk aversion, and females being more risk averse than males. Subjects were also found to subjectively distort probabilities, where subjects would overweight low probabilities and underweight moderate to high probabilities. Expected Utility models and Rank-Dependent Utility models show that risk and trust are statistically significantly related and that the reasons for trusting one's partner may have arisen out of an inner need to simply trust that person. In addition, risk preferences were able to predict trusting decisions in the environment of risk and the environment of trust. Risk and trust therefore go hand-in-hand and it can be argued that trusting decisions are perceived as decisions involving risk. This study therefore finds that trusting decisions are in fact confounded by risk attitudes, so that a subject may be seen as trusting when actually they are just risk-seeking, or seen as non-trusting when they are just simply risk averse.